Viral load, tissue distribution and histopathological lesions in goats naturally and experimentally infected with the Small Ruminant Lentivirus Genotype E (subtype E1 Roccaverano strain). (June 2018) - Grego, E.; Reina, R.; Lanfredini, S.; Tursi, M.; Favole, A.; Profiti, M.; Lungu, M.M.; Perona, G.; Gay, L.; Stella, M.C.; DeMeneghi, D.
Abstract: Small Ruminant Lentivirus (SRLV) subtype E1, also known as Roccaverano strain, is considered a low pathogenic virus on the basis of natural genetic deletions, in vitro properties and on-farm observations. In order to gain more knowledge on this atypical lentivirus we investigated the in vivo tropism of Roccaverano strain in both, experimentally and naturally infected goats. Antibody responses were monitored as well as tissue distribution and viral load, evaluated by real time PCR on single spliced ( gag/env ) and multiple spliced ( rev ) RNA targets respectively, that were compared to histopathological lesions. Lymph nodes, spleen, alveolar macrophages and mammary gland turned out to be the main tissue reservoirs of genotype E1-provirus. Moreover, mammary gland and/or mammary lymph nodes acted as active replication sites in dairy goats, supporting the lactogenic transmission of this virus. Notably, a direct association between viral load and concomitant infection or inflammatory processes was evident within organs such as spleen, lung and testis. Our results validate the low pathogenicity designation of SRLV genotype E1 in vivo, and confirm the monocyte-macrophage cell lineage as the main virus reservoir of this genotype. Accordingly, SRLV genotype E displays a tropism towards all tissues characterized by an abundant presence of these cells, either for their own anatomical structure or for an occasional infectious/inflammatory status. Highlights: Small Ruminant Lentivirus Genotype E (subtype E1 Roccaverano strain) as a low pathogenic virus Viral load, tissue distribution, histopathological lesions of SRLV genotype E in goats naturally and experimentally infected Roccaverano strain Organs and tissues tropism